2023
DOI: 10.1111/acel.13780
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A activators reverse age‐related behavioral changes by targeting neural cell senescence

Abstract: The contribution of cellular senescence to the behavioral changes observed in the elderly remains elusive. Here, we observed that aging is associated with a decline in protein phosphatase 2A (PP2A) activity in the brains of zebrafish and mice. Moreover, drugs activating PP2A reversed age‐related behavioral changes. We developed a transgenic zebrafish model to decrease PP2A activity in the brain through knockout of the ppp2r2c gene encoding a regulatory subunit of PP2A. Mutant fish exhibited the behavioral phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Specifically, at 10 mpi, there was a suppression of the protein PPP2R2A, an enzyme involved in the dephosphorylation of intracellular proteins 61 , and MTHFD2, which plays a role in RNA metabolism and translation 62 . Previous research has demonstrated that the downregulation of protein phosphatase leads to cell senescence in aging zebrafish neuronal cells 63 , and the suppression of MTHFD2 has been linked to cell death in infectious hematopoietic necrosis virus (IHNV)-infected zebrafish larvae 64 . Thus, the suppression of these proteins in infected RHTiB cells indicates that TiLV may inhibit host cell replication and metabolism early in the infection process, which facilitates viral entry and replication, as seen with other viruses, such as influenza A virus, hepatitis B, and Epstein-Barr virus (EBV) 61,[65][66][67] .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, at 10 mpi, there was a suppression of the protein PPP2R2A, an enzyme involved in the dephosphorylation of intracellular proteins 61 , and MTHFD2, which plays a role in RNA metabolism and translation 62 . Previous research has demonstrated that the downregulation of protein phosphatase leads to cell senescence in aging zebrafish neuronal cells 63 , and the suppression of MTHFD2 has been linked to cell death in infectious hematopoietic necrosis virus (IHNV)-infected zebrafish larvae 64 . Thus, the suppression of these proteins in infected RHTiB cells indicates that TiLV may inhibit host cell replication and metabolism early in the infection process, which facilitates viral entry and replication, as seen with other viruses, such as influenza A virus, hepatitis B, and Epstein-Barr virus (EBV) 61,[65][66][67] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, some repurposed drug molecules have demonstrated new seno‐modulator characteristics, besides their classical mechanism of action. For example, the psychostimulant and anti‐depressant methylphenidate (MPH); its primary action is to activate dopamine release, but it is also able to activate the protein phosphatase 2A (PP2A), a neuronal protein whose activity decreases in the aging brain of zebrafish and mice 18 . Activated PP2A has anti‐senescent properties in the neurons of these two species but might be also related to the fact that polymorphisms of the PP2A gene predispose human subjects to mental illness and cognitive impairment 19 that can be attenuated by MPH treatment at advanced ages 20 .…”
Section: Figurementioning
confidence: 99%
“…For example, the psychostimulant and anti‐depressant methylphenidate (MPH); its primary action is to activate dopamine release, but it is also able to activate the protein phosphatase 2A (PP2A), a neuronal protein whose activity decreases in the aging brain of zebrafish and mice. 18 Activated PP2A has anti‐senescent properties in the neurons of these two species but might be also related to the fact that polymorphisms of the PP2A gene predispose human subjects to mental illness and cognitive impairment 19 that can be attenuated by MPH treatment at advanced ages. 20 From this point of view, PP2A remains a promising gero‐target but the real effects of its activation in preventing neuronal aging in humans are yet to be better documented.…”
mentioning
confidence: 99%